RIGHT PADDLE REPAIR METHODS FOR IMPROVING TRAFFIC SAFETY AT TRAIN RAILWAY TRACKS - Dian Novitasari; Ratna Handayani (Universitas Islam Malang, 2022)
Problems that often occur at level crossings with railroads are the high number of trafficaccidents, namely accidents between trains and vehicles, two-wheeled vehicles that fall dueto inadequate railroad infrastructure, and the condition of road pavements at level crossingsthat are not stable. This study is focused on handling pavement damage at railroadcrossings, especially at the JPL 67 location, which is located on the East Java Provinceroad, UPT area. Road and Bridge Management (PJJ) Surabaya, namely Jalan DepartemenKrian –Mojokerto Regency (link. 153) Km. 30. At the level crossing of JPL 67, two-wheeledmotor vehicle accidents often occur. There is a significant difference in elevation betweenthe highway and the railroad, causing damage to the pavement. The problem is tried to beovercome by conducting a study by UPT. PJJ Surabaya. This study aims to obtain the rightroad handling method according to the character of the load on level crossings, namelydynamic loads on train vibrations. Several road handlings trials have been carried out fromJanuary 2022 to June 2022, using several pavement materials. The study found that CTBwith a cement composition can make the pavement at level crossings last longer.